Complete mitochondrial genome sequence of Thryssa kammalensis (Clupeiformes, Engraulidae). Issue 1 (1st January 2016) - Zhao, Liangjie; Liu, Qigen
Abstract: In this paper, the complete mitochondrial DNA (mtDNA) sequence of Thryssa kammalensis was determined. The mitochondrial genome is 16, 884 bp in length, including 13 protein-coding genes, 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs), and a non-coding control region as those found in other vertebrates, with the gene identical to that of typical vertebrates. The overall base composition of the heavy strand is 31.07% A, 24.82% T, 28.33% C, and 15.78% G, with an AT bias of 55.89%. Phylogeny of T. kammalensis suggested more close relationship with Lycothrissa crocodilus and Setipinna taty . The complete mitogenome of this species can provide a basic data for the studies on population history, molecular systematics, phylogeography, stock evaluation, and conservation genetics.